2002
DOI: 10.1046/j.1420-9101.2002.00408.x
|View full text |Cite
|
Sign up to set email alerts
|

Caucasus Mountains divide postulated postglacial colonization routes in the white-breasted hedgehog, Erinaceus concolor

Abstract: For many European species, the mountains of the Alps and the Pyrenees have acted as significant barriers to northwards colonization from southern glacial refugia. To the east, the Caucasus Mountains would seem to have been a similar barrier to the white‐breasted hedgehog (Erinaceus concolor). A deep divergence among hedgehog mitochondrial sequences to the north and south of the Caucasus Mountains suggests two colonization routes, originating from separate refugial regions and divided by this mountain barrier. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
65
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 23 publications
2
65
0
2
Order By: Relevance
“…As insectivores, the hedgehogs were undoubtedly greatly influenced by climate-dependent changes in the availability of insect food during the Quaternary period and the dramatic range dynamic must have left clear imprints in the genetic architecture of this taxon (Santucci et al, 1998;Seddon et al, 2001Seddon et al, , 2002Berggren et al, 2005). Recently, three species of the genus Erinaceus were recognised in the western Palearctic (Aulagnier et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As insectivores, the hedgehogs were undoubtedly greatly influenced by climate-dependent changes in the availability of insect food during the Quaternary period and the dramatic range dynamic must have left clear imprints in the genetic architecture of this taxon (Santucci et al, 1998;Seddon et al, 2001Seddon et al, , 2002Berggren et al, 2005). Recently, three species of the genus Erinaceus were recognised in the western Palearctic (Aulagnier et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The range of northern white-breasted hedgehogs (Erinaceus roumanicus) covers Eastern Europe and Ponto-Mediterranean regions and likely originated in the Balkan refugium. The range of southern white-breasted hedgehogs (E. concolor) includes Asia Minor and Levant, but it is isolated from the range of E. roumanicus by the Bosporus Strait and Caucasus Mountains (Seddon et al, 2002). Although the imprints of glacial oscillations are obvious, the roots of the divergence are Pliocene (3.2-4.5 Myr; Seddon et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Temperate species, which presently occupy central and northern Europe, mainly derive from Mediterranean refugium populations that underwent range expansion in the late glacial and early post-glacial periods (Hewitt, 1996), with a western form deriving from an Iberian refugium and an eastern form from the Italo-Balkanic refugium (Dumolin-Lapegue et al, 1997;Ferris et al, 1993Ferris et al, , 1998Santucci et al, 1998;Thorpe, 1984). Several authors, however, suggest an additional mode of colonisation of central and northern Europe by non-Mediterranean populations, coming from one or more eastern refugia: Caucasus, southern Ural, central Europe, and western Asia (Bilton et al, 1998;Cooper et al, 1995;Michaux et al, 2004;Nesbo et al, 1999;Palme and Vendramin, 2002;Seddon et al, 2002). A few other species (BrunhoV et al, 2003;Taberlet et al, 1998) …”
Section: Introductionmentioning
confidence: 99%
“…A deep split between hedgehogs and their eastwest and north-south subdivisions based on genetic data (Santucci et al, 1998;Suchentrunk et al, 1998;Seddon et al, 2001Seddon et al, , 2002 suggests the strong effects of climate on the current distribution of their genetic variation and indicates different refugia history and expansion patterns (Berggren et al, 2005). The Balkans has been identified as the most likely refugium of E. roumanicus (Seddon et al, 2002;Bolfíková and Hulva, 2012). The northward expansion route of E. roumanicus from the Balkans into central Europe followed a pattern of vegetation expansion; however, previous studies found a slightly divergent lineage in Austria, Hungary, and western Russia, which indicated that there may have been more than one route from the Balkans to the north (Seddon et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The Balkans has been identified as the most likely refugium of E. roumanicus (Seddon et al, 2002;Bolfíková and Hulva, 2012). The northward expansion route of E. roumanicus from the Balkans into central Europe followed a pattern of vegetation expansion; however, previous studies found a slightly divergent lineage in Austria, Hungary, and western Russia, which indicated that there may have been more than one route from the Balkans to the north (Seddon et al, 2002). Seddon et al (2001) indicated that refugia populations existed rather as a series of small isolated populations due to spatial variability in climate, as suggested by pollen data (Huntley, 1999).…”
Section: Introductionmentioning
confidence: 99%